Pembelajaran Audio Visual Selama Pandemi Covid-19 Di TK Kana Ungaran - Kristanti, Diana; Purwanto, Hary; Wenas, Maria Lidya (Sekolah Tinggi Teologi Simpson Ungaran, 2021)
Learning activities have an essential role in improving learning, which serves to see how understanding students receive new knowledge from the teaching and learning process, especially during the Covid-19 pandemic with audiovisual materials at Kana Ungaran Integrated Kindergarten. The type of research used is descriptive quantitative (survey). The data collection method used a questionnaire. The results showed that: (1) aspects of children's learning activities in participating in the learning process in terms of prayer (93%) were stated to be very active; (2) then the observing aspect (76%) can be noted that children are involved in online learning; (3) then the aspect of remembering (94%) can be stated that the child is very active in participating in the learning process in terms of placing; and (4) the next aspect is understanding (66%) can be stated that they are pretty active in the learning process. From the research results, the lowest aspect is understanding (66%), and the highest aspect is remembering (94%). This study suggests that teachers and parents work together and entrust the child to the supervisor during the online learning process.